KORELASI ANTARA INTENSI TURNOVER, KEPUASAN KERJA DAN STRES KERJA PADA KARYAWAN PT. X JAMBI - Kusnadi, Dedek (Heuristic, 2015)
This study was conducted to determine: (1) the correlation between job satisfaction and turnover intention of employees of PT. X Jambi, (2) the correlation between job stress and turnover intention of employees of PT. X Jambi and (3) the correlation between job satisfaction and job stress on employees of PT. X Jambi. The results of the study are (1) between job satisfaction and turnover intention has a negative correlation was weak and not significant, it is shown by the value of the correlation coefficient of -0.295 and opportunities are not mutually correlated 0.065 greater than the maximum terms are correlated by 0.025. It can be concluded between job satisfaction and turnover intention has not had a meaningful relationship, (2) the correlation between job satisfaction and job stress also has a weak positive correlation was not significant, it is shown by the value of the correlation coefficient of 0.024 and opportunities are not mutually correlation of 0.882 is greater than the maximum terms are correlated 0.025, (3) the correlation between job stress and turnover intention has a significant positive relationship, it is shown by the value of the correlation coefficient of 0.381 and opportunities are not mutually correlated by 0,015 less than the requirement maximum mutual correlation of 0.025. It can be concluded between job stress and turnover intention is to have a meaningful relationship.Kata kunci : korelasi, intensi turnover, kepuasan kerja, stres kerja